The Construction of the Waduk Gajah Mungkur and its Influence on the Socio-Economic Development of the Wonogiri Community - Rizky Ahmad Abudan; Hieronymus Purwanta (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
Infrastructure development during the New Order era served as one of the state’s instruments for driving economic growth and social transformation. One such strategic project was the construction of the Gajah Mungkur Reservoir in Wonogiri Regency, Central Java. This study aims to analyse the background to the construction of the Gajah Mungkur Reservoir and its impact on the socio-economic development of the Wonogiri community from the perspective of state-led development. The research employs a historical method with a qualitative approach through four stages: heuristics, source criticism, interpretation and historiography. The research sources consist of government archives, development reports, statistical data from the Central Statistics Agency (BPS), contemporary newspapers, as well as various secondary sources in the form of relevant books and academic articles. The research findings indicate that the construction of the Gajah Mungkur Reservoir was not only driven by the need for water resource management and flood control, but also formed part of the state’s development strategy to address structural issues in Wonogiri, such as low agricultural productivity, limited water resources, poverty, and high labour out-migration. The existence of the reservoir has brought about socio-economic changes, including increased irrigation-based agricultural productivity, the emergence of new economic sectors such as fisheries and tourism, and rising community incomes. On the other hand, it has led to social changes in the form of population relocation and changes to people’s livelihoods. It can therefore be concluded that the construction of the Gajah Mungkur Reservoir has had an impact on the socio-economic sector of the Wonogiri community.